MYTHOLOGY IN ORAL LITERATURE AND IMPLICATIONS TO THE EXISTENCE OF LOCAL WISDOM IN DISTRICT VII KOTO SUNGAI SARIAK PADANG PARIAMAN DISTRICT: MITOLOGI DALAM SASTRA LISAN DAN IMPLIKASI TERHADAP EKSISTENSI KEARIFAN LOKAL DI KECAMATAN VII KOTO SUNGAI SARIAK KABUPATEN PADANG PARIAMAN - Romi Isnanda; Yetty Morelent; Hasnul Fikri; Rio Rinaldi (Jurnal Kata, 2022)
The purpose of this study is to explain the social functions contained in the mythology/folklore that exist and their implications for the existence of local wisdom in District VII Koto Sungai Sariak, Padang Pariaman. The theory as the reference was proposed by Hasanuddin WS (in Sutriarti et al., 2012). Collecting data by recording and distributing questionnaires. The data were analyzed by means of (1) transcription, (2) transliteration, (3) grouping based on the research focus. Based on the results of data analysis and discussion, it can be concluded that first, mythology/folklore is full of social values and functions in people's lives; second, the results of the questionnaire distribution, namely (1) people who understand the function and importance of maintaining local wisdom 80.3%; (2) people who view local wisdom as limited to the performing arts of the Cultural Studio 64.6%; (3) stories obtained from the elders 21.8%; (4) oral literature does not need to be preserved because it is 18.4% outdated. Thus, the existence of oral literature still needs attention for the community, in District VII Koto Sungai Sariak, Padang Pariaman.